Researching Translator's Functional Style - Wu, Kan. author. (orcid)0000-0002-4411-1410 Link aut Link
XVII, 189 p. 63 illus., 43 illus. in color.
Keywords: This book introduces an innovative approach to studying translator style through the lens of functional linguistics and corpus stylistics. It examines how translators recreate essential textual functions in target texts, focusing on three key aspects: thematic reconstruction, recharacterization, and textual panorama building. Through a detailed case study of Chinese-English translations of Lao She's Er Ma, the book demonstrates how translators' functional styles manifest in their strategic linguistic choices. This work advances corpus-assisted translation studies by shifting focus from formal linguistic features to their functional roles in shaping translated texts.